The Impact of Knowledge-Based Economy Indicators on Economic Growth (Case Study: Selected Persian Gulf Countries) - Al-Gharabi, Naeem Hameed Mahood; Daei-Karimzadeh, Saeed; Alshemari, Salam Mounam Zamil; hafezi, Bahar (Business, Marketing, and Finance Open, 2024)
The knowledge-based economy can bring numerous benefits to societies and nations. Through knowledge-driven production, the possibility of enhancing economic growth and improving economic conditions in societies arises, with economic growth subsequently leading to wealth creation and increased economic welfare. Additionally, countries are witnessing the emergence of knowledge-based, technology-driven businesses, which exhibit the highest growth rates and aim to capture the largest share of global markets, thereby contributing to the development and consolidation of a knowledge-based economy. Therefore, given the significant effects of the knowledge-based economy on broader economic outcomes and growth, the purpose of this study is to analyze the impact of knowledge-based economy indicators on the economic growth of selected Perisan Gulf countries during the period 2010 to 2022. To this end, the Generalized Method of Moments (GMM) approach was employed. The results indicated that institutional quality—as a component of economic incentives and institutional systems within a knowledge-based economy—has a positive and significant effect on economic growth. Similarly, innovation—as a core of the innovation and technology system—human capital and active labor force—as pillars of education and workforce skills—and the level of personal internet use and the security of internet servers—as elements of information infrastructure and communication technologies—also positively and significantly influence the economic growth of the selected Persian Gulf countries.